Anandamide, Acting via CB2 Receptors, Alleviates LPS-Induced Neuroinflammation in Rat Primary Microglial Cultures - Natalia Malek; Katarzyna Popiolek-Barczyk; Joanna Mika; Barbara Przewlocka; Katarzyna Starowicz (Neural Plasticity)
Microglial activation is a polarized process divided into potentially neuroprotective phenotype M2 and neurotoxic phenotype M1, predominant during chronic neuroinflammation. Endocannabinoid system provides an attractive target to control the balance between microglial phenotypes. Anandamide as an immune modulator in the central nervous system acts via not only cannabinoid receptors (CB1 and CB2) but also other targets (e.g., GPR18/GPR55). We studied the effect of anandamide on lipopolysaccharide-induced changes in rat primary microglial cultures. Microglial activation was assessed based on nitric oxide (NO) production. Analysis of mRNA was conducted for M1 and M2 phenotype markers possibly affected by the treatment. Our results showed that lipopolysaccharide-induced NO release in microglia was significantly attenuated, with concomitant downregulation of M1 phenotypic markers, after pretreatment with anandamide. This effect was not sensitive to CB1 or GPR18/GPR55 antagonism. Administration of CB2 antagonist partially abolished the effects of anandamide on microglia. Interestingly, administration of a GPR18/GPR55 antagonist by itself suppressed NO release. In summary, we showed that the endocannabinoid system plays a crucial role in the management of neuroinflammation by dampening the activation of an M1 phenotype. This effect was primarily controlled by the CB2 receptor, although functional cross talk with GPR18/GPR55 may occur.